Catechins decrease neurological severity score through apoptosis and neurotropic factor pathway in rat traumatic brain injury - Ratnawati, Retty; Arofah, Annisa Nurul; Novitasari, Anastasia; Utami, Sartika Dewi; Hariningsih, Made Ayu; Rahayu, Masruroh; Rianawati, Sri Budhi; Purnomo, Hari; Dalhar, Mochammad (Faculty of Medicine, Trisakti University, 2017)
BACKGROUNDCatechins inhibits apoptosis through anti oxidant and anti inflamation pathway. Catechins also increases brain-derived neurotrophic factor (BDNF). There was a few research that explained the role of catechins in traumatic brain injury (TBI). The objective of the study was to evaluate the effect of catechins administration on neurologic severity score (NSS) through apoptosis and neurotropic pathway in traumatic brain injury rat model.METHODSA post test only controlled group design was performed using traumatic brain injury rat (Rattus novergicus) model through weight drop models. It was devided into negative control group, positive control group, TBI+catechins 513 mg/kgBW, TBI+catechins 926 mg/kgBW, TBI+catechins 1113 mg/kgBW. NSS was measured in the first hours, day three, and day seven. The expressions of NFkB, TNFa, Bcl-2, Bax, caspase 3, caspase 8, BDNF, and the numbers of apoptosis cells were evaluated by imunohistochemystry method. One way Anova and Kruskal Wwallis were used to analyse the data.Results TNFa, caspase 8, number of apoptosis cells were significantly decreased on the seventh day administration compared to the third day administration (p<0.05). Catechins increased the expression of Bcl-2/Bax and BDNF significantly (p<0.05). Yet, there were no significant differences between expression of caspase 3, NSS, Bcl-2/Bax ratio, and BDNF toward third days administration of catechins compared with seven days administration (p>0.050).ConclusionsAdministration of catechins decreased NSS through inhibiting inflammation and apoptosis, as well as induced the neurotrophic factors in rat brain injury. Catechins may serve as a potential intervention for TBI.